The Mexico-Belgium Drug Trafficking on the Rise of Criminal: Belgium as the New Drug Capital of Europe - Verodova, Ave; Apriani, Devi; Annindya, Jasmine; Aulia, Sabina; Satria, Randhi (Mandala: Jurnal Ilmu Hubungan Internasional, 2023)
Belgium has recently come under international spotlight due to its reputation for drug trafficking across Europe. One of Belgium's ports, Antwerp, is home to the largest cocaine drug trafficking operation organized by drug-gang working with suppliers from other parts of Europe. In 2022, drug shipments through the Port of Antwerp recorded 110 tons of cocaine. The drug products were distributed and smuggled from Mexico. This kind of transnational organized crime harms the countries that it is aimed to distribute. Public security in Belgium is at risk due to crimes involving cartels and the distribution of illegal goods from many countries. Therefore, this research was conducted to analyze the question of how drug trafficking in Belgium affects the crime activity of Belgium societies, especially in the 2021-2022 period. This research is a qualitative study that uses descriptive methods by taking secondary data sources using library research techniques such as from journal, news, government websites, and other credible sources. The study finds that drug trafficking from Mexico has affected the rise of crime in Belgium, such as bribery of officials and corruption in port customs officials, death threats and terror to those who do not want to cooperate, killing of innocent people as a result of street shootings and house burnings, and even there are threats against high officials such as the Belgian prime minister and minister of justice at a higher level. This paper will contribute to the drug trafficking pool of study and crime related drugs in Europe, especially Belgium.